Successful treatment of a prosthetic hip infection due to Enterococcus faecalis with sequential dosing of oritavancin and prosthesis preservation without prosthetic joint surgical manipulation. (2020) - Nguyen, Jullian P.; Contreras, Brian X.; Sierra-Hoffman, Miguel; Saddler, Kim; Stevens, Mark L.; Castro-Lainez, Miriams T.; Knox, Brett; Deliz, Rafael J.
Abstract: A patient with a prosthetic joint infection (PJI) complicated with deep surgical site infection due to vancomycin-susceptible Enterococcus faecalis. The initial treatment consisted of 10 days with daptomycin plus ampicillin. The hip prosthesis was retained and salvaged with six outpatient sequential doses of oritavancin 1200 mg every seven days without intra-articular irrigation or other surgical interventions. The patient was ambulating independently without symptoms after ten months of the last treatment of oritavancin.